EXPERIMENTAL STUDY ON TURNING WITH SELF-PROPELLED ROTARY CUTTING TOOL - Emiroglu, U.; Kiyak, M.; Altan, E. (YILDIZ TECHNICAL UNIV, 2017)
In metal cutting, self-propelled rotary tools in which the contact zone between tool and workpiece continuously changes have been used in recent years. The previous researchers used the self-propelled rotary cutting tools specially designed and manufactured for experimental study. This study presents an experimental investigation to evaluate the performance of a new designed and manufactured self-propelled rotary cutting tool. The experiments were realized by turning mild steel under different cutting parameters in order to determine the flank wear and the surface roughness. It has been seen that the new designed cutting tool has major advantage over stationary cutting tool providing longer tool life, but poor workpiece surface quality.
Keywords: Self -Propelled Rotary Cutting Tool; Flank Wear; Surface Roughness; AEROENGINE ALLOYS; SURFACE QUALITY; WEAR; STEEL; Thermodynamics